Value of Colonial Architectural Heritage for Sustainable Tourism Promotion in Center of Thakhek City - SENGONKEO, Luangphasy; SIHAVONG, Saikhim; SYHALATE, Phisit; INSYXIENGMAI, Sithixay; PHONGKHAMDENG, Phaichit (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to study the value of the colonial architectural heritage in the center of the old town of Thakhek to promote sustainable tourism with an emphasis on historical, cultural and economic values. The research method is document survey and field survey to present information on the value of colonial architectural heritage in descriptive and analysis method. The results of the study found that 1) Historical, cultural and social values, 2) The value of urban planning and urban structure, 3) Architectural and scenic value, 4) Architectural heritage value and 5). The value of using and promoting heritage and cultural tourism. The research also proposes a way to promote sustainable tourism that involves the participation of all relevant parties including the local community, government agencies and tourism businesses, implementing environmental policies, promoting cultural preservation, supporting the local economy, create sustainability certification standards for tourism businesses, monitor and evaluate economic, social and environmental impacts and create awareness campaigns. The research highlighted the importance of preserving colonial buildings in order to promote tourism, increase cultural identity, and promote economic development. This study has contributed to the understanding of colonial architectural heritage preservation and the impact of sustainable development in the region.